2012
DOI: 10.1007/s00572-012-0453-z
|View full text |Cite
|
Sign up to set email alerts
|

Influence of different mineral nitrogen sources (NO−3-N vs. NH+4-N) on arbuscular mycorrhiza development and N transfer in a Glomus intraradices–cowpea symbiosis

Abstract: Labeled nitrogen (15 N) was applied to a soil-based substrate in order to study the uptake of N by Glomus intraradices extraradical mycelium (ERM) from different mineral N (NO3− vs. NH4+) sources and the subsequent transfer to cowpea plants. Fungal compartments (FCs) were placed within the plant growth substrate to simulate soil patches containing root-inaccessible, but mycorrhiza-accessible, N. The fungus was able to take up both N-forms, NO3− and NH4+. However, the amount of N transferred from the FC to the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
34
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 51 publications
(34 citation statements)
references
References 43 publications
0
34
0
Order By: Relevance
“…Although the positive effect of the AM symbiosis on P nutrition is long known, the contribution of AM fungi to N nutrition of their host plant is still under debate (Smith & Smith, ). However, there is increasing evidence that AM fungi can deliver substantial amounts of N to their host plant, even if the percentage contribution to total N nutrition of the host can vary considerably and is context dependent (Ngwene, Gabriel, & George, ). We found that when the fungus had access to an exogenous 15 N source, 15 N was delivered to the host, and the shoot biomass and N concentrations in the roots increased (Figures a, d and a,b).…”
Section: Discussionmentioning
confidence: 99%
“…Although the positive effect of the AM symbiosis on P nutrition is long known, the contribution of AM fungi to N nutrition of their host plant is still under debate (Smith & Smith, ). However, there is increasing evidence that AM fungi can deliver substantial amounts of N to their host plant, even if the percentage contribution to total N nutrition of the host can vary considerably and is context dependent (Ngwene, Gabriel, & George, ). We found that when the fungus had access to an exogenous 15 N source, 15 N was delivered to the host, and the shoot biomass and N concentrations in the roots increased (Figures a, d and a,b).…”
Section: Discussionmentioning
confidence: 99%
“…These different biochemical capacities and, hence, light saturated photosynthetic rates can be influenced by AMF, because they depend on leaf [N], [P] (Braune et al 2009; Niinemets et al 2005; Walker et al 2014) and protein mass fractions (Onoda et al 2005; Yamori et al 2010). Depending on source and amount of available nutrients, elevated leaf P mass fractions are frequent phenomena in mycorrhizal plants (Augé 2001; Ngwene et al 2010, 2013; Nouri et al 2014), but N mass fractions in leaf tissues have been variable, being higher, unchanged or lower depending on the setting (Augé 2001; Grimoldi et al 2006; Leigh et al 2009; Ngwene et al 2013; Nouri et al 2014). Thus, the biochemical model parameters closely related to nutrition such as J max change in mycorrhizal plants (Adolfsson et al 2015; Fini et al 2011; Romero-Munar et al 2017).…”
Section: Discussionmentioning
confidence: 99%
“…Although AM fungi are able to take up different forms of N, not all forms of N are transferred equally to the plant. Indeed, Ngwene et al (2012) found out that more 15 N was transferred to cowpea plants when the AM fungus Glomus intraradices had access to labelled nitrate compared to ammonium. Contradictory results were obtained by Tanaka and Yano (2005) who showed that the AM fungus Glomus aggregatum can rapidly deliver N derived from ammonium to maize plants but not from nitrate.…”
Section: B Ammonium Transport In Ecto-and Arbuscularmentioning
confidence: 98%